Development of an educational chatbot with a contextual intent system on the dialogflow platform - Ivashchenko, Oksana Vitaliivna; Filip, Stanislav; Ratushnyi, Bohdan Volodymyrovych (Національний технічний університет "Харківський політехнічний інститут", 2025)
In the context of digital transformation in higher education, the development of intelligent agents capable of maintaining continuous and effective interaction with students is becoming increasingly relevant. This article presents a complete life cycle of the creation of the contextual chatbot “Pytayko z PIITU” for the Department of Software Engineering and Intelligent Control Technologies of NTU “KhPI”. The chatbot is designed to provide quick and intuitive access to information about academic procedures, communication channels, scholarships, documents, and other common questions related to students' interaction with the department and its website. The system was developed using the Dialogflow platform with Telegram integration and Google Cloud Functions as the fulfillment handler. The core of the system is a structured multi-level intent architecture, where each intent group corresponds to a thematic category such as admissions, documents, or course schedules. This allows the bot to maintain conversation context, ensure precise routing of requests, and reduce ambiguity in user interaction. The prototyping model was selected as the life cycle methodology due to the need for active user feedback and iterative improvement. У контексті цифрової трансформації вищої освіти дедалі більшої актуальності набуває розробка інтелектуальних агентів, здатних забезпечувати безперервну та ефективну взаємодію зі студентами. У статті представлено повний життєвий цикл створення контекстно-залежного чат-бота "Питайко з ПІІТУ" для кафедри програмної інженерії та інтелектуальних технологій управління НТУ "ХПІ". Бот призначено для швидкого та інтуїтивного доступу до інформації про навчальні процеси, канали зв’язку, стипендії, документи та інші типові запитання, що виникають під час взаємодії студентів з кафедрою та її вебсайтом. Система розроблена на платформі Dialogflow з інтеграцією до месенджера Telegram та використанням Google Cloud Functions як засобу обробки запитів (fulfillment). Ядро системи становить структурована багаторівнева система інтентів, кожна з яких відповідає певній тематичній категорії (наприклад, вступ, документи, розклад занять). Така архітектура дозволяє підтримувати контекст діалогу, забезпечувати точне маршрутизування запитів та зменшувати неоднозначність взаємодії. У якості моделі життєвого циклу було обрано прототипування, що дозволило враховувати зворотний зв’язок користувачів і вдосконалювати систему ітеративно.
Розробка освітнього чат-бота з контекстною системою інтентів на платформі Dialogflow
Keywords: chatbot development; higher education; student services; prototyping model; intent system; fallback logic; natural language understanding; розробка чат-бота; вища освіта; студентські сервіси; модель прототипування; система інтентів; fallback-логіка; обробка природної мови